ROLE OF FILLER IN POROZED ARBOLT - Turapov Farkhod Khursanovich (Galaxy International Interdisciplinary Research Journal, 2022)
In a market economy, the problem is especially acute for enterprises that produce modern energy-saving building materials, such as foam concrete, polystyrene concrete, etc. from rising cement prices. The reason for this is the increased (compared to traditional materials) consumption of high-quality cement and, as a result, high selling prices for finished wall materials. However, the need for energy-saving building materials is very high today. One of the ways to solve this problem is to master the production of porous building materials, in particular, porous wood concrete based on a multicomponent binder.